Love, infatuation and Compromise in Austen’s Pride and Prejudice - Ashfaq, Samina; Khattak, Nasir Jamal (The Journal of Humanities & Social Sciences, 2015)
In Pride and Prejudice, we see skilful management of different types of feelings between men and women and their effects on the life of those involved. Love, infatuation and compromise are revealed through the relationships of different characters and their actions which reflect their state of mind and helps the reader to analyse and judge their degree of contentment. The happy characters prove that for an ideal relationship sincere love is essential; for then one is morally and ethically satisfied. There are those who consider worldly gains as the ultimate source of happiness. For them physical comfort and superficial assurance of a happy life is the ultimate gain. However there are some who consider peace of mind, sound morals and union based on trust and understanding as a source of true happiness. The desire for wealth among different social classes does not matter when it comes valuing relationships based on material gains. The poor want to acquire wealth and the rich want to have more. For this they are ready to implement fair or foul means without any regard for truth, honesty or morality. Though they achieve their goals yet at a price they are destined to regret forever because then there is no going back.